Understanding urban ecology : exploring the ecological integrity of small scale greening interventions in the City of Cape Town - Avlonitis, Georgina (Department of Environmental and Geographical Science, 2014)
This research explores the ecological integrity of three small-scale interventions in urban greening in a single catchment in the City of Cape Town, within the Cape Flats Sand Fynbos ecotype. The chosen intervention sites were namely: Tokai Park, Princess Vlei and Bottom Road Sanctuary. The study aimed to bridge a gap in the current research by contributing to an understanding of the ecological value of social management and intervention.